2020
DOI: 10.1186/s12884-020-2837-y
|View full text |Cite
|
Sign up to set email alerts
|

Male involvement in prevention of mother to child transmission of human immunodeficiency virus and associated factors in Enebsiesarmider District, north West Ethiopia, 2018: a cross-sectional study

Abstract: Background: Globally, male involvement has been identified as a priority target area to be strengthened in the prevention of mother to child transmission (PMTCT) of HIV. However, there are limited studies on husband involvement in the prevention of mother to child transmission of HIV in Ethiopia. Therefore, this study aimed to assess male involvement in the prevention of mother to child transmission of HIV and associated factors among males whose wives gave birth in the last six months before the survey in Ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
7
5
0
Order By: Relevance
“…Knowing the service provided at the PMTCT clinic increased MPI by 3.25 times. This nding is in line with other studies [10,27,35]. The MPI in HTC was 3.17 times higher among MP who knew at least one timing of MTCT.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Knowing the service provided at the PMTCT clinic increased MPI by 3.25 times. This nding is in line with other studies [10,27,35]. The MPI in HTC was 3.17 times higher among MP who knew at least one timing of MTCT.…”
Section: Discussionsupporting
confidence: 92%
“…Our study found that MPI in HTC is increased with increasing educational levels. This nding is in line with other studies [10,27,30]. Educated men may have more information regarding the advantage of getting the service provided at the health facility.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This number varies regionally, in North America and Europe 15%, in Asia and Pacific countries 29%, in Caribbean countries 34%, in Western and North Africa 42%, and in Eastern and South Africa 26% of people living with HIV do not know their status. 5 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…This number varies regionally, in North America and Europe 15%, in Asia and Pacific countries 29%, in Caribbean countries 34%, in Western and North Africa 42%, and in Eastern and South Africa 26% of people living with HIV do not know their status. 5,7 According to a CDC report from 2016-2018, about 1,700,998 persons were tested for HIV using contact index testing among 20 countries. From those tested, 5.8% were reported as HIV-positive, including 9.8% aged ≥15 years and 1.5% aged <15 years.…”
Section: Introductionmentioning
confidence: 99%